Avaliação do desenvolvimento do inseto Diaphorina Citri através da alimentação em dieta artificial contendo Cistatinas de citros - Fan, Karina (Universidade Federal de São Carlos, 2023)
Brazil is an essentially agricultural country, being highlighted in citriculture worldwide, especially in the production and export of citrus in natura and concentrated juice. Despite its economic relevance, the crops are severely affected by pests and pathogens, many of which have few effective control measures. Huanglongbing (HLB), known as greening in some countries, is considered the most serious and destructive disease of citrus, affecting growth, ripening, and fruit morphology. The causal agents of HLB are phloem-limited bacteria of the species Candidatus Liberibacter spp. that are transmitted by the Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Liviidae). As a consequence of HLB, the fruits are characterized by low juice content and high acidity, which make their commercialization unfeasible and lead to serious economic losses. Currently, HLB control is done by monitoring seedlings and using chemicals, but it is a laborious method and not always effective, and may generate insect resistance. Thus, new technologies are needed, and the development of plants overexpressing inhibitors of cysteine-peptidases (cystatins) is an interesting alternative. Hemiptera use several proteases in their digestive process, mainly of the cysteine-peptidase type and, therefore, the interaction between cystatins and cysteine-peptidases can affect the growth and development of pest insects. Thus, this study aimed the heterologous expression of recombinant cystatins from Citrus clementina (CclemCPI-1 and CclemCPI-3) and Citrus sinensis (CsinCPI-2) in Escherichia coli and purification by affinity chromatography. These purified proteins were used to evaluate the inhibitory activity in artificial diet for D. citri, at concentrations of 1 and 2 mg/mL, in order to observe any effect on the psyllid development. In the tests performed in artificial diet containing the 3 purified proteins, a considerable mortality rate was observed for CclemCPI-1 protein, with 26.97% at 1 mg/mL and 48% at 2 mg/mL. In the assays with CclemCPI-3 and CsinCPI-2 proteins, mortality of 6 and 8%, respectively, was observed at the highest concentration. These data suggest a possible interference in insect development. However, further tests will be necessary to standardize the results, as well as to investigate the cystatin-peptidase interaction and evaluate for dose-dependence
Evaluation of insect Diaphorina citri development feeding by artificial diets containing recombinant cystatins from Citrus
Keywords: Citros; HLB; Diaphorina citri; Cistatina; Dieta artificial; Citrus; Huanglongbing; Cystatin; Artificial diet; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR